Elite athletes` experiences of musculoskeletal pain management using neuroanatomical dry needling: A qualitative study in Swedish track and field - Thompson, R.; Prosell, M.; Timpka, T. (Journal of Science and Medicine in Sport, 2021)
To investigate how elite track and field athletes with a history of musculoskeletal pain (MSKP) describe their perceptions of clinical treatments based on dry needling guided by a neurological map (neuroanatomical dry needling (naDN)). Design: Qualitative study. Methods: In-depth interviews were conducted with eight elite Swedish track and field athletes (6 males, 2 females, median age 28.5) treated at a clinic specialised in MSKP management. All interviews were audio recorded and transcribed verbatim. The data were structured and analysed using a thematic method. Results: The athletes approached clinical MSKP treatment from a performance-orientated perspective. They explained that they inevitably suffered MSKP episodes due to the intense physical demands of their sport. The use of naDN was considered an integral part of their sports practice and the study clinic's services were readily utilised when MSKP caused minor reductions in physical capacity. The athletes appreciated an unambiguous anatomical diagnosis, preferably supported by imaging scans, as this increased their confidence in clinical services. They valued the naDN treatment as it was perceived to provide fast-acting analgesia that enabled rapid return-to-play. These factors combined to reduce performance-related stress. Conclusions: Elite track and field athletes with a history of MSKP sought and appreciated clinical treatment with naDN largely because it provided fast-acting analgesia that enabled rapid return-to-play at a high-performance level. These athletes` expectations of MSKP diagnosis and management appear incongruent with current research indicating that MSKP sensitivity within the nervous system does not accurately reflect musculoskeletal tissue state or recovery following tissue damage.